Quantitative Proteomic Analyses Identify ABA-Related Proteins and Signal Pathways in Maize Leaves under Drought Conditions - Zhao, Yulong; Wang, Yankai; Yang, Hao; Wang, Wei; Wu, Jianyu; Hu, Xiuli (Frontiers in Plant Science, 2016)
Drought stress is one of major factors resulting in maize yield loss. The roles of abscisic acid (ABA) have been widely studied in crops in response to drought stress. However, more attention is needed to identify key ABA-related proteins and also gain deeper molecular insights about drought stress in maize. Based on this need, the physiology and proteomics of the ABA-deficient maize mutant vp5 and its wild-type Vp5 under drought stress were examined and analyzed. Malondialdehyde content increased and quantum efficiency of photosystem II decreased under drought stress in both genotypes. However, the magnitude of the increase or decrease was significantly higher in vp5 than in Vp5. A total of 7051 proteins with overlapping expression patterns among three replicates in the two genotypes were identified by Multiplex run iTRAQ-based quantitative proteomic and liquid chromatography-tandem mass spectrometry methods, of which the expression of only 150 proteins (130 in Vp5, 27 in vp5) showed changes of at least 1.5-fold under drought stress. Among the 150 proteins, 67 and 60 proteins were up-regulated and down-regulated by drought stress in an ABA-dependent way, respectively. ABA was found to play active roles in regulating signaling pathways related to photosynthesis, oxidative phosphorylation (mainly related to ATP synthesis), and glutathione metabolism (involved in antioxidative reaction) in the maize response to drought stress. Our results provide an extensive dataset of ABA-dependent, drought-regulated proteins in maize plants, which may help to elucidate the underlying mechanisms of ABA-enhanced tolerance to drought stress in maize.